Key Elements of the Research Proposal - Tiwari, Liladhar (Journal of Nepalese Management and Research, 2023)
This article gives deep insight into the elements of a research proposal. This article provides a comprehensive overview of the main elements that must be comprised in a well-shaped research proposal. It has tried to examine the key elements of the research proposal. The major objective of this study is to indicate what the researcher proposes to explore, which is important enough to deserve the enquiry and the suitable method to make an original contribution. It helps develop a general idea about the academic research proposal. Furthermore, it provides and allows readers to assess the research proposal’s basic premises quickly. It helps the readers deliver an overview of the information about the contents of the research proposal. It should summarize all the basic parts of information and explanation like title, abstract, statement of the problem, objective, review of literature, hypothesis or research questions, research methodology, research plan, timeline, budget, and limitation of the study, reference and appendix.